La prensa sensacionalista y su impacto en los habitantes del Sector San Francisco Número 2 del Cantón Valencia año 2019 - Jurado Fuertes, Jonathan Javier (2020)
The sensationalist media are characterized by disseminating controversial, shocking or attention-grabbing information, to the detriment of other matters or objectively more important aspects of such matters. It is common that sensationalist media tends to repeatedly pour false or harmful information. The sensational current was created to produce sensations, emotions and curiosity in the public. There are media that seek to get the attention of the public, reporting in an exaggerated way the facts, this type of pompous writing has a simple writing, understandable to any reader; It has a range of colors that highlights its headlines making them flashy; they also choose images that cause people morbidity, that produce curiosity for wanting to know more about the news. The press as sensationalism in Ecuador, has been growing in society as an unstoppable phenomenon, taking root the same that has not stopped until today, where they use striking elements, the same that is identified with the popular classes, where the only thing that seeks It is to satisfy the curiosity to satisfy the morbidity, forgetting its objective that is to educate and guide the population.